Pedagogical features of the development of sociocultural competence in the process of Rural Education - Nataliia Piddubna; Inna Pavlova; Oleksandr Iievliev; Iryna Tamozhska; Natalia Varga (Universidade Federal do Norte do Tocantins, 2022)
The main purpose of the study is to determine the main features of the pedagogical aspects of sociocultural competence as an element of intercultural communication. Sociocultural competence involves the inclusion of students in intercultural communication, modeled in the classroom in rural education. The implementation of intercultural communication presupposes an adequate mutual understanding of communication participants who are representatives of different cultures. The development of psychological and pedagogical theory and practice has led to increased attention to the formation of sociocultural competence of students in the process of their professional training in rural education. The methodology includes a number of theoretical and research bibliographic methods. First of all, methods of analysis and synthesis of scientific and practical information were applied. The method of systematization and abstract-logical was also applied. As a result, the key aspects of sociocultural competence were identified as an element of the psychology of intercultural communication. Further development is needed on issues related to the formation of sociocultural competence in future students and the use of interdisciplinary connections in the process of their professional training in rural education.